Effects of Bush Sophora Root polysaccharide and its sulfate on DHAV-1 replication. (1st October 2018) - Chen, Yun; Yang, Yuhui; Yuan, Wenjuan; Wang, Zhaohui; Ming, Ke; Zeng, Ling; Liu, Jiaguo
Highlights: This is the first report of the anti-DHAV replication mechanism of BSRPS and sBSRPS. Influences of BSRPS and sBSRPS on DHAV-1 3D protein stability were first studied. Inhibition effects of BSRPS and sBSRPS on Hsp70 expression were first reported. Inhibition effects of BSRPS and sBSRPS on DHAV-1 IRES activity were first reported. Abstract: Duck hepatitis A virus type 1 (DHAV-1) is a mortal virus to ducklings under three weeks old. Bush sophora root polysaccharide (BSRPS) and its sulfate, sulfated BSRPS (sBSRPS), inhibited the replication of DHAV-1. However the detailed mechanisms were still unknown. The protein translation and RNA synthesis are two most important steps of the replication. Additionally, DHAV-1 3D protein, cellular Hsp70 protein, and DHAV-1 IRES were the important regulatory factors. Therefore, the influence of BSRPS and sBSRPS on DHAV-1 protein translation and RNA synthesis were studied. RT-qPCR, western blot, and dual-luciferase reporter system were used to study the inhibition mechanisms of BSRPS and sBSRPS on DHAV-1. The results showed both BSRPS and sBSRPS significantly inhibited the DHAV-1 protein translation and RNA synthesis, and the effect of sBSRPS was stronger. Furthermore, they dropped the protein translation via suppressing DHAV-1 IRES activity and dropped the DHAV-1 synthesis via suppressing cellular Hsp70 expression.